2019
DOI: 10.1016/j.ebiom.2019.07.050
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: MicroRNA-134 prevents the progression of esophageal squamous cell carcinoma via the PLXNA1-mediated MAPK signalling pathway

Abstract: Background: MicroRNAs (miRNAs) are involved in oncogenesis of esophageal squamous cell carcinoma (ESCC). miR-134 is reported to have a tumour-suppressive role but its role in ESCC is not known. The present study was designed to examine whether miR-134 inhibits ESCC development and further explored relevant underlying mechanisms. Methods: Differentially expressed genes related to ESCC were identified from microarray gene expression profiles. Immunohistochemical staining and RT-qRCR assays identified elevated PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Similarly, miRNAs also play a significant regulatory role in ESCC. For instance, miR‐134 can restrain ESCC progression via downregulating PLXNA1 to block the MAPK signaling pathway . MiR‐488‐3p negatively modulates ZBTB2 and activates the p53 pathway to exert its anti‐cancer effect in ESCC .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, miRNAs also play a significant regulatory role in ESCC. For instance, miR‐134 can restrain ESCC progression via downregulating PLXNA1 to block the MAPK signaling pathway . MiR‐488‐3p negatively modulates ZBTB2 and activates the p53 pathway to exert its anti‐cancer effect in ESCC .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miR-134 can restrain ESCC progression via downregulating PLXNA1 to block the MAPK signaling pathway. 17 MiR-488-3p negatively modulates ZBTB2 and activates the p53 pathway to exert its anti-cancer effect in ESCC. 18 Additionally, miR-149-5p is downregulated in multiple tumors, such as gastric cancer, non-small cell lung cancer, and osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant reports have shown that gene PLXNA1, which is signi cantly co-expressed with gene SPTBN2, is involved in the MAPK pathway. Silencing the expression of gene A can enhance cell apoptosis in esophageal squamous cell carcinoma, block cell cycle, inhibit cell growth, removal, and invade (32).Immunoin ltration analysis showed that the expressions of DAPK1 and DMXL2 DAPK1 and DMXL2 are likely to play an signi cant role in the research of immune cell in ltration and is a biomarker for the prognosis of patients with colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal cancer (EC) is one of the most common gastrointestinal malignancies and ranks as the sixth most important cause of cancer mortalities globally, with an estimated 509,000 new deaths every year (1,2). As one of the most common histologic subtypes of EC, ESCC usually composes over 90% of all EC cases in parts of Asia and Sub-Saharan Africa (1,3). Although remarkable advances in surgical treatments, chemotherapy, and radiotherapy for ESCC, the 5-year overall survival rate is still <20%, due to the high incidences of tumor metastasis (4,5).…”
Section: Introductionmentioning
confidence: 99%